Ekstraksi Minyak Atsiri pada Daun Jeruk Manis (Citrus Aurantium) dengan Menggunakan Metode Microwave Hydrodistilation (MHD) - Putri Agustin, Mawardhi Nabilla; Andreyan Poerwo Negoro; Ditta Kharisma Yolanda Putri; Meta Fitri Rizkiana; Istiqomah Rahmawati (Program Studi Teknik Kimia Universitas Jember, 2023)
This study aims to utilize sweet lime leaves which are only waste that has no value, where sweet lime leaves are one of the ingredients that contain essential oils. Apart from the skin, it turns out that this sweet lime leaf can also be extracted using the Microwave Hydrodistillation (MHD) method. This study uses three variables namely; the F/S ratio used was 0.375 g/mL; 0.5g/mL; 0.65 g/mL, power 150 watts, 300 watts, and 450 watts, and time 30, 60, and 90 minutes. The extraction method is carried out using fresh ingredients with a solvent volume of 200 ml. The test carried out is the GC-MS test. The results of the test method and the purpose of this study were to determine the limonene content in the extraction of sweet lime leaves using the MHD method with variations in ratio, power, and time. The optimum yield of essential oils is at a power of 300 W, 90 minutes, and a ratio of 0.625 with a yield of 0.373%. The biggest components produced in the MHD method of extracting citrus leaves were Germacrene D 29.51%, Alpha-Copaene 18.47%, CIS-CAROPHYLNE 15.42%, 9-Eicosene (E) 8.58% and Limonene 5.51%.